Myth and emotions - Lipscomb, Antonella; Losada-Goya, José-Manuel (Cambridge Scholars Publishing, 2017)
The emotive nature of myth lays the foundation of the research proposed for this trilingual volume. The book provides a thorough and multifaceted study that offers guidelines and models capable of interpreting mythical-emotional phenomena. It represents a major contribution to a more informed understanding of an important part of the writing and art of modernity and post-modernity, as well as cultures and thought of contemporary society.